Pengembangan Alogaritma Pengolahan Citra untuk Menghindari Rintangan pada Traktor Tanpa Awak - Usman Ahmad; Desrial .; I Dewa Made Subrata; Sjahrul Annas (Jurnal Keteknikan Pertanian, 2010)
AbstractUnmanned tractors, even though it uses global positioning system (GPS) technology to identify the working path, still require an ability to recognize the environment in front of it in order to avoid obstacles thatmay exist. A device that can be used to recognize the environment in front of the tractor and avoid obstacles that may exist, is the camera. However, images captured by the camera need to be processed to detect possible obstacles at the front of the tractor. This study aimed to develop image processing algorithms to detect the possible presence of obstacles on the path to be traversed by an unmanned tractor, and directed the tractor to a safe path by giving the new coordinates when there are obstacles in front of it. Several mage processing techniques such as edge detection, opening and closing, marking free area, and the determination of the coordinates were used for the purpose of directing the path in front of the tractor when there are obstacles that must be avoided.Keywords: image processing, obstacles, unmanned tractor, algorithmsDiterima: 19 April 2010; Disetujui: 18 Oktober 2010